Antioxidant activity and total Phenolic content of fruits and vegetables commonly found in the Filipino diet (2005)
The antioxidant activities and total phenolic contents of edible portions of 27 eaten fresh fruits and vegetables in the Philippines, including green leafy vegetables, other vegetables, fruits and root crops were determined. The antioxidant activity, expressed in terms of the rate by which β-carotene undergoes bleaching, varied from 0 to 76%. Among the plant groups studied, root crops had the highest antioxidant activity at 68.51% on the average. The total phenolic content, measured as mg catechin equivalents (CE) per 100 g sample based on the Folin-Ciocalteau method, ranged from 0 to 2015. Kamote (Ipomoea batatas) leaves had the highest total phenolic concentration at 2015 mg CE per 100 g sample. No linear correlation exists between the antioxidant activity and total phenolic content of the samples. However, a strong significant correlation was observed when the samples were considered within a group. The equivalent vitamin E (400 IU) antioxidant activity of the samples was likewise determined.
Keywords: Vegetables; Fruits